(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2021)
Some considerations on the experience of Colonel Carlo Alberto dalla Chiesa in Palermo between 1966 and 1973 are proposed here. During this period dalla Chiesa commanded the Carabinieri Legion in the Sicilian capital, giving new impetus to investigations into the Mafia. The article retraces some of the investigative innovations introduced by dalla Chiesa in the fight against organised crime, starting from his hearing before the antimafia Parliamentary Committee on 4 November 1970, which is reported hereafter. In particular, it underlines the Colonel’s enhancement of the in-depth analysis of mafia crime and his emphasis on the limits of the penal mechanism of the time.